Nonlinear Short-Run Adjustments between House and Stock Prices in Emerging Asian Regions - Fang, Hao; Lee, Yen-Hsien; Chang, William S. (Panoeconomicus, 2018)
This study uses the powerful nonparametric cointegration test to examine whether nonlinear cointegration exists between prices of used houses and corresponding stock markets in China and the four Asian Tigers. Then, it uses the smooth transition vector error-correction model (STVECM) to explore the adjustment efficiencies of the short-run house and corresponding stock-return dynamics when there is disequilibrium between house and stock prices. The empirical results indicate that there is nonlinear cointegration between the house prices and corresponding stock prices in China, South Korea, Singapore, and Taiwan, and that the speed of price adjustment to equilibrium is always greater for houses than stocks when there are large positive and negative deviations. Moreover, the short-run speed of adjustment of the large negative and positive deviations is equal in China, South Korea, and Taiwan, but unequal in Singapore. With the exception of South Korea, the results of the Granger causality test indicate that stock prices clearly lead used house prices, which means a wealth effect exists in most Asian countries. Our study confirms that the STVECM can be used to analyze the short-run adjustment efficiency of house and stock return dynamics in China, South Korea, Singapore, and Taiwan; thus, supporting models of interaction between noise and arbitrage traders. Key words: China, Four asian tigers, Smooth transition Vector Error-Correction Model, Nonparametric co-integration, Price discovery. JEL: C32, C51, C52, D53, G11, R31. Ovo istraživanje koristi moćni neparametarski test kointegracije da bi se ispitalo da li postoji nelinearna kointegracija između cena korišćenih kuća i odgovarajućih berzi u Kini i četiri Azijska Tigra. Zatim, koristi se glatko prelazni modeli korekcije ravnotežne greške (STVECM) za ispitivanje efikasnosti prilagođavanja kratkoročne veze između kuća i odgovarajuće dinamike povraćaja akcija kada postoji neravnoteža između cene kuća i akcija. Empirijski rezultati ukazuju na to da postoji nelinearna kointegracija između cena kuća i odgovarajućih cena akcija u Kini, Južnoj Koreji, Singapuru i Tajvanu, kao i da je brzina prilagođavanja cena prema ravnoteži uvek veća za kuće nego za akcije kada postoje velika pozitivna i negativna odstupanja. Štaviše, kratkoročna brzina prilagođavanja velikih negativnih i pozitivnih odstupanja jednaka je u Kini, Južnoj Koreji i Tajvanu, ali nejednaka u Singapuru. Naša analiza potvrđuje da se STVECM može koristiti za analizu efikasnosti kratkoročnog prilagođavanja kuća i povratka akcija u Kini, Južnoj Koreji, Singapuru i Tajvanu; tako, podržava modele interakcije između šuma i arbitražnih trgovaca. Ključne reči: Kina, četiri Azijska Tigra, glatko prelazni modeli korekcije ravnotežne greške, neparametrijska kointegracija, otkrivanje cena.